(untitled) (International Journal of Advanced Research in Computer Science, 2017)
This work demonstrates the application of decision tree, as data mining tool, in the health care system. Data mining has the capability for classification, prediction, estimation, and pattern recognition by using health databases. Databases of health systems contain significant information for decision making. It could be properly revealed with the application of appropriate data mining techniques. Decision trees are employed for identifying valuable information in health databases. In this paper Decision tree as a data mining tools is used for predication the spread types of disease of hepatitis virus in reigns that high affect to people with different temperature and prevention of this disease by using rules that needed to predicate the diseases . Â Keywords:- Decision Tree Modeling, Healthcare Data Mining Applications, Decision Rule Induction.